Domain-specific Internet use and social participation in older adults: the role of affective attitudes toward digital device use. - Memmer, Nicole; Kniepkamp, Sophie; Schlomann, Anna; Schmidt, Laura I.; Krönung, Julia; Schubert, Anna-Lena; Wahl, Hans-Werner (European Journal of Ageing, 2026)
Internet use plays an important role in social participation in later life, yet little is known about how different domains of Internet use are linked to social outcomes or which factors shape engagement in these domains. Using an integrative approach, this study examines cognitive and affective attitudes toward Information and Communication Technology (ICT), age, and gender as predictors of social, informational, and entertainment-related Internet use and investigates how these domains relate to subjective (loneliness) and objective (social activity) indicators of social participation. Data were drawn from the baseline assessment of the SMART-AGE randomized controlled trial, comprising 648 community-dwelling adults aged 67–93 years (M = 75.0, SD = 5.63; 52% female). The proposed structural equation model showed good fit to the data. Positive affective but not cognitive attitudes as well as younger age were significantly correlated with all three Internet use domains. Male gender was associated with greater informational and entertainment Internet use, but not with social use. Among the Internet use domains, social use was linked to lower loneliness, informational use was positively associated with social activity, and entertainment use was negatively associated with social activity. Taken together, these findings highlight the importance of affective attitudes in shaping engagement in different forms of Internet use and contribute to a more nuanced understanding of how different forms of Internet use are related to social participation in later life.